Dendrobium huoshanense polysaccharides ameliorate ulcerative colitis by improving intestinal mucosal barrier and regulating gut microbiota. (September 2022) - Yu, Jiao; Zhao, Junwei; Xie, Huiqun; Cai, Ming; Yao, Liang; Li, Jinmiao; Han, Lan; Chen, Weidong; Yu, Nianjun; Peng, Daiyin
Graphical abstract: Highlights: Long-term administration of DHP improved symptoms of UC mice. DHP improved intestinal mucosal barrier function and reduced inflammation. DHP regulated intestinal microecological disorders. DHP effectually restored abnormal metabolism in the intestinal flora of UC mice. Abstract: The gut microbiota is inextricably linked to ulcerative colitis (UC). The therapeutic effect of Dendrobium huoshanense polysaccharides (DHP) on ulcerative colitis has been confirmed, but whether it acts through the intestinal flora is still unknown. The study aimed to investigate the potential mechanisms of DHP intervention in UC mice by combining metabolomics of intestinal contents and gut flora analysis. The results showed that DHP alleviated UC symptoms while improving colonic mucosal barrier function and inflammatory manifestations. A total of 12 potential biomarkers were significantly altered in metabolomics concerning tryptophan metabolism, vitamin B6 metabolism, regulation of sodium reabsorption by aldosterone, and steroid hormone biosynthesis. DHP reversed the abundance of Fusobacteriota, Deferribacterota and Bacteroidetes, and significantly increased Desulfobacteriota . DHP significantly decreased the relative abundance of Clostridioides, while increasing Alistipes, and Rikenella. In conclusion, through metabolomics and 16s RNA sequencing methods, we explored the mechanism of preventive effects of Dendrobium huoshanense on UC.